Park Algorithm as Predictor of Premature Ventricular Contraction Origin in Three‐Dimensional Mapping Electrophysiological Studies - Amir, Muzakkir (Int J Gen Med, 2020)
PURPOSE: In the past few years, premature ventricular contraction (PVC) has attracted immense attention, both in patients with or without structural heart disease. Despite the technological advancement, no guiding tools are currently available to assist in the prediction of origin of PVC using a 12‐lead electrocardiogram (ECG) before electrophysiology and ablation procedures. Park and co‐workers compiled the existing algorithms for the morphology of ECG from the literature and generated a single algorithm based on specific features of ECG for the prediction of PVC origin. The Park algorithm is limited to idiopathic PVC and has not been evaluated clinically. In the present study, the Park algorithm was used to predict PVC origin in patients with or without structural heart disease and compared with the gold standard examination based on three-dimensional electrophysiological mapping studies. PATIENTS AND METHODS: A cross‐sectional study employing ECG data and electrophysiology study (EPS) reports from patients’ medical records at Integrated Heart Center Wahidin Sudirohusodo Hospital, Makassar, Indonesia was conducted. The study was performed from April 2018 to June 2019 with a total of 31 samples; however, four samples were excluded during the EPS. RESULTS: In the present study, the incidence of structural heart disease was 45.2%. The suitability of the Park algorithm for electrophysiological evaluation was 85.2%, both in the case of PVC with and/or without structural heart disease. The prediction of the origin of PVC in the right or left heart using the Park algorithm showed a sensitivity of 95%, specificity of 100%, positive predictive value of 100%, negative predictive value of 87.5%, and accuracy of 96%. CONCLUSION: The findings of the study suggest significant accuracy of the Park algorithm in the prediction of location of origin of PVC. High sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of the Park algorithm highlight its suitability to be used for determining the location of PVC origin in the right or left heart.